Pengaruh Audit Manajemen Dan Kualitas Pengendalian Intern Terhadap Kinerja Manajerial Dengan Good Corporate Governance Sebagai Variabel Moderasi - Ni Nengah Suharwini; Akram Akram; Lalu M. Furkan (Universitas Mataram, 2022)
This study aims to analyze the effect of management audit and the quality of internal control on managerial performance with good corporate governance as a moderating variable. The population of this study were 106 managerial level officials and auditors at PT Bank NTB Syariah. The data analysis tool uses an interaction test. The results show that management audit and quality of internal control have a significant effect on managerial performance, but good corporate governance if it is a moderating variable does not strengthen the influence of management audit and quality of internal control on managerial performance, but good corporate governance has a direct and significant positive effect on managerial performance. This research has implications for the authorities to determine further steps and policies related to managerial performance.